Anemia hemolítica autoinmune después de la infección por Covid 19 - Telmo Coelho; João Miranda; Raquel Moura; Paula Ferreira (Sociedade Galega de Medicina Interna, 2023)
Since its emergence in Wuhan province in late 2019, SARS-CoV-2 infection has affected more than 520 million people and caused the death of more than 6.2 million individuals. Despite rare, several haematological disorders have been observed and associated with SARS-CoV-2 infection, in particular, autoimmune haemolytic anaemia (AIHA). We present the case of a 71-year-old man with recent SARS-CoV-2 infection, presenting with 5 weeks evolution of asthenia and loss of 10% of body weight. From the initial study, normochromic normocytic anaemia stands out with haptoglobin consumption. Direct Coombs test was positive, with positive direct antiglobulin test for IgG4. The patient was admitted and started corticosteroids therapy with prednisolone 1 mg / kg. Given that the extended etiologic study was negative, covid 19 was assumed to be the trigger of the current clinical picture. During hospitalization, the patient presented a favourable evolution with recovery of haemoglobin value and absence of haemolysis.